Knowledge Level and Application of Animal Welfare Aspects at Binjai City Slaughterhouse (Talenta Publisher, 2022)
Animal welfare is very important to pay attention to in the slaughtering process in abattoirs to ensure the quality of the meat produced. This study aims to determine the level of knowledge of the implementers of the activities on aspects of animal welfare and the application of animal welfare aspects at the Binjai City Slaughterhouse. This research was conducted at the Binjai City Slaughterhouse, Jalan Letan Umar Baki, Clove Turi, North Binjai District, Binjai City, from October to November 2021. This study used a survey method: interviews and direct observation with the implementers of activities at the Slaughterhouse. Binjai City Animals consists of 3 cattle traders, 15 animal controllers, and one slaughterer using a questionnaire and a checklist. This study uses an assessment based on a Likert scale. Based on the results of the study, the level of knowledge regarding aspects of animal welfare from the implementers of activities at the Binjai City Slaughterhouse was in the sound and excellent categories. In the application of animal welfare aspects at the Binjai City Slaughterhouse to the facilities it has, it is categorized as very good (100%) in slaughter facilities and good category (80%) in animal shelter facilities.